DETERMINATION OF THE REAL VALUES OF KINEMATIC INDEX CORRESPONDING TO THE MECHANICAL SEPARATION PROCESS - EMILIAN MOȘNEGUȚU; VALENTIN NEDEFF; MIRELA PANAINTE-LEHĂDUȘ; NARCIS BÂRSAN; DANA CHIȚIMUȘ; DRAGOȘ RUSU (Journal of Engineering Studies and Research)
This article presents the methodology for determining the real values of kinematic indices which characterizes the mechanical separation of a mixture of solid particles. Mechanical separation of a mixture of solid-solid on surface provided with holes is the most common method of separation. To optimize equipment that performs this operation, both theoretical and practical characteristics are determined. Kinematic indices are part of the theoretical characteristics, helping to identify behavior of solid particles on a surface flat swing. Starting from an experimental batch, real values of the kinematic indices corresponding to up, down and sideways movement on the sieve were determined for the following types of real particles: grain, large grain beans, small grain beans and soybeans.